Risk Factors of Infection and Transmission of Viral Hepatitis B and E - Osadolor, Aisosa J; Osadolor, Owens O; Osadolor, Obehi O (Mediscope, 2023)
Viral hepatitis is a disease burden in Africa and globally. It can be caused by RNA or DNA virus, which is hepatotropic and can pose a financial burden on the individual, their family, and society. Hepatitis B virus (HBV) is a DNA virus that can be present in blood and body fluids, including saliva, semen, and vaginal secretion. It is par-enterally transmitted with horizontal and vertical transmission. The risk of infection and transmission of hepatitis B virus infection could be a result of occupational exposure, use of unsterilized blades for traditional and cultural practices in Africa like tribal marks, level of awareness on prevention and adherence to standard or universal precautions. The risk of infection and transmission of hepatitis B virus infection also includes individual sexual history, the availability and access to vaccines, the level of occupational hazards exposure, the level of vaccine acceptance and the vaccination status of individuals. Hepatitis E virus (HEV) is a single-stranded RNA virus that is transmitted through the faeco-oral route by consumption of contaminated food and water. Low socio-economic status, poor environmental sanitation, poor water supply, poor sewage disposal facilities, level of awareness on prevention, poor social condition and decreased personal hygiene are associated factors for the risk of hepatitis E virus infection. Knowledge and community-based awareness and practice of World Health Organization (WHO) preventive practices and treatments could reduce the burden of hepatitis B and E virus infections. Mediscope 2023;10(2): 89-92